Identification of induced mutants for morpho-physiological and biochemical traits of rajmash (Phaseolus vulgaris) - BHAGAT, SHILPA; KUMAR, SANJEEV; DOGRA, SAPALIKA (The Indian Journal of Agricultural Sciences, 2023)
An experiment was conducted during rainy (kharif) seasons of 2019 and 2020 at the Regional Horticultural Research Station, Bhaderwah of Shere Kashmir University of Agriculture Sciences and Technology, Jammu to characterize the 24 induced mutants of rajmash (Phaseolus vulgaris L.) to study the genetic diversity among them. Experimental material consisted of 22 induced mutants generated through gamma irradiation and 2 land races, viz. Bhaderwah Local and Poonch Local. Twenty-two induced mutants were grouped into 8 clusters, and 5 clusters on the basis of biochemical and morpho-physiological traits, respectively. Majority of which were accommodated in cluster I (13) followed by cluster II (4) and minimum in cluster V (1). Further, cluster I showed the largest intra-cluster distance (D2=39.10), followed by cluster V, and the remaining clusters having the shortest intra-cluster distance (D2= 0.00). Cluster II and III had the least distance between them, whereas cluster III and V had the greatest inter-cluster distance (D2=9.36). Among the morpho-physiological characters studied grain yield/plant (53.26%), days to 50% flowering (7.25%), days to maturity (0.72%), seeds/pod (3.62%), pods/plant (9.78%), pod length (4.35%), clusters/ plant (18.84%) and 1000-seed weight (2.17%), contributed 99.99% to the total divergence. Likewise, in biochemical characters protein content (1.81%), zinc content (38.04%) and iron content (22.46%) were studied. Inter-cluster distances were larger than intra-cluster distances for biochemical traits, indicating that there was a significant degree of genetic variation among the mutant lines and these lines can be used in hybridization for rajmash improvement programme.